1997
DOI: 10.1086/304610
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Polarization in the Taurus Dark Clouds: Wavelength‐dependent Position Angles and Cloud Structure near TMC‐1

Abstract: Systematic variations with wavelength in the position angle of interstellar linear polarization of starlight may be indicative of multiple cloud structure along the line of sight. We use polarimetric observations of two stars (HD 29647, HD 283809) in the general direction of TMC-1 in the Taurus Dark Cloud to investigate grain properties and cloud structure in this region. We show the data to be consistent with a simple two-component model, in which general interstellar polarization in the Taurus Cloud is produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
5
21
0
Order By: Relevance
“…As discussed earlier, both stars show intrinsic polarization and rotation in their polarization angle. In both the cases, the polarization angle seems to decrease with increasing wavelength, which is similar to observations in Messinger et al (1997) toward the direction of Taurus dark cloud.…”
Section: Determination Of Distance To L1570supporting
confidence: 86%
“…As discussed earlier, both stars show intrinsic polarization and rotation in their polarization angle. In both the cases, the polarization angle seems to decrease with increasing wavelength, which is similar to observations in Messinger et al (1997) toward the direction of Taurus dark cloud.…”
Section: Determination Of Distance To L1570supporting
confidence: 86%
“…Such a wavelength dependence is similar to the Serkowski law (Serkowski et al 1975) and the Wilking law (Wilking et al 1982) and is often found in the aperture polarimetry of T Tauri stars (e.g. Hodapp 1984;McGreor et al 1994;Messinger et al 1997;Whittet et al 2001;Pereyra et al 2009). We would like to point out that Serkowski's and Wilking's laws are intended to fit the interstellar polarization, where the polarization is produced by dichroic extinction, and the above similarity is met by chance.…”
Section: Effects Of the Disk Height And The Grain Sizesupporting
confidence: 74%
“…Linear interstellar polarization is observed to peak at wavelengths in the visible or near-infrared along different lines of sight, and a close correlation between these peak wavelengths and the maximum size of the aligned grains is predicted by interstellar extinction models. Longer peak wavelengths are found mostly in denser clouds (Messinger et al 1997), pointing toward larger grains there. However, for the wavelength of maximum polarization to be a unique indicator of maximum grain size, grains of all sizes must be aligned with equal efficiency in all environments, and grains of all sizes must be nonspherical to the same degree.…”
Section: X-ray Halos As Tracers Of Large Interstellar Grainsmentioning
confidence: 93%
“…These include the wavelength of peak linear interstellar polarization (e.g., Messinger, Whittet, & Roberge 1997), the dust albedo at near-infrared wavelengths (Kim, Martin, & Hendry 1994;Witt, Oliveri, & Schild 1990;Lehtinen & Mattila 1996;Witt et al 1994), and the shape and intensity of X-ray halos surrounding point sources of X-rays (Mauche & Gorenstein 1986;Mathis & Lee 1991;Predehl & Klose 1996). Linear interstellar polarization is observed to peak at wavelengths in the visible or near-infrared along different lines of sight, and a close correlation between these peak wavelengths and the maximum size of the aligned grains is predicted by interstellar extinction models.…”
Section: X-ray Halos As Tracers Of Large Interstellar Grainsmentioning
confidence: 99%